Effect of E-Commerce, Use of Accounting Information Systems and Business Capital in Student Decision Making for Entrepreneurship - Choirina Nurlaila; Hadiah Fitriyah (Indonesian Journal of Law and Economics Review, 2021)
The research has a purpose to determine the effect of the variables (1)E-commerce, (2)the use of accounting information systems and (3)business capital on student decision making for entrepreneurship. The research method uses quantitative. The study used primary data with a questionnaire. Students of the accounting study program at Muhammadiyah Sidoarjo University with as many as 88 respondents were the population in this study. Used purposive sampling technique in determining the sample.assistance software SPSS version 23.0in data processing. In analyzing the data using multiple linear regression method. The results of the study prove that (1)E-commerce and (2)the use of accounting information systems have an influence on students' decision making for entrepreneurship, while (3)Business capital has no influence on entrepreneurial decisions.